Using Aggregate Vasoactive-Inotrope Scores to Predict Clinical Outcomes in Pediatric Sepsis - Shah, Palak; Petersen, Tara L.; Zhang, Liyun; Yan, Ke; Thompson, Nathan E. (Frontiers in Pediatrics, 2022)
Objectives: Sepsis is one of the most common causes of pediatric morbidity and mortality. The heterogeneity of this disease makes it difficult to predict outcomes using existing severity of illness tools. The vasoactive-inotrope score (VIS) is a quantitative measure of the amount of vasoactive support required by patients. We sought to determine if a higher aggregate VIS over the first 96 hours of vasoactive medication initiation is associated with increased resource utilization, worsened clinical outcomes, and increased risk of in-hospital complications in pediatric patients with severe sepsis. Design: Retrospective cohort study. Setting: Single-center at Children’s Wisconsin in Milwaukee, WI. Patients: Two-hundred pediatric patients, age less than 18 years old, diagnosed with severe sepsis, receiving vasoactive medications with Time 0, onset of vasoactive medications, between January 2017 and July 2019. Interventions: Retrospective data obtained from the electronic medical record, calculating VIS at 2h intervals from 0-12h and at 4h intervals from 12-96h from Time 0. Measurements: Aggregate VIS derived from the hourly VIS area under the curve (AUC) calculation based on the trapezoidal rule. Data analyzed using Pearson’s correlations, Mann-Whitney test, Wilcoxon signed rank test, and classification and regression tree (CART) analyses. Main Results: Higher aggregate VIS is associated with longer hospital LOS (p<0.0001), PICU LOS (p<0.0001), MV days (p=0.018), increased in-hospital mortality (p<0.0001), in-hospital cardiac arrest (p=0.005), need for ECMO (p<0.0001), and need for CRRT (p<0.0001). CART analyses found that aggregate VIS >20 is an independent predictor for in-hospital mortality (p<0.0001) and aggregate VIS >16 for ECMO use (p<0.0001).